Just money : mission-driven banks and the future of finance - Kaufer, Katrin; Steponaitis, Lillian K. (Lillian Kazimiera) (Cambridge, Massachusetts : The MIT Press, 2021)
"An accessible exploration of the role of mission-driven banks in the future of finance"--
OCLC-licensed vendor bibliographic record.
Keywords: elektronické knihy; electronic books; Financial institutions -- Social aspects; Banks and banking -- Social aspects; Social responsibility of business; Social change; BUSINESS/Social Responsibility; ECONOMICS/Finance